Pengaruh Motivasi Intrinsik dan Kepuasan Kompensasi Terhadap Kinerja Karyawan Dengan Semangat Kerja Karyawan Sebagai Variabel Intervening Di PT Latinusa Kota Cilegon - Hapsari, Desy Retno; Kambara, Roni (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
PT Latinusa is the one of tinplate producer in Indonesia. PT Latinusa manufacturing and fulfill tinplate need for need consumtion need material in domestic market. In a company human resources is important element that must have good performance. Created health company can doing with motivating the officer and increase satisfaction compensation until increase work spirit that have impact to increase performance. The purpose of this research is to know as much as impact positive direct of : intrinsic motivation to performance, compensation satisfaction to performance, intrinsic motivation to work spirit, compensation satisfaction to work spirit and work spirit to performance. This research is causalitas and quantitative research, with research location is PT Latinusa, Cilegon City. Sample in this research is worker as much as fourty people. This research is use Structural Equation Modelling (SEM) analysis with software SmartPLS. Data that collective consist primary and secondary data. Primary data from questioner and secondary data from documentary and library learning. Calculation statistic result from SEM is 81,4 % intirinsic motivation and compensation satisfaction influential to work spirit and 82% intrinsic motivation , compensation satisfaction and work spirit influential to performance. See intrinsic motivation, compensation satisfaction and work spirit have high impact to performance, so one of method to increase performance is increase intrinsic motivation, compensation satisfaction and work spirit.